Effectiveness of buerger-allen exercise on lower extremity perfusion and peripheral neuropathy symptoms among patients with diabetes mellitus - Jinna Radhika; Geetha Poomalai; SiralaJagadeesh Nalini; Ramanathan Revathi (Wolters Kluwer Medknow Publications, 2020)
Background: Buerger-Allen Exercise (BAE) promote Lower Extremity Perfusion (LEP) via the wound healing process and reduce Peripheral Neuropathy Symptoms (PNS) among Diabetes Mellitus (DM) patients. We study the efficacy of BAE on LEP and PNS among patients with DM. Materials and Methods: This quasi-experimental study was conducted prospectively from July to October 2017. Fifty DM patients between the ages of 30 and 75 from both genders were selected using a purposive sampling technique and were assessed for LEP with a manual Ankle-Brachial Index (ABI) scale and assessed for PNS with Michigan Neuropathy Screening Instrument (MNSI). The BAE was demonstrated for 4 consecutive days. The intervention was repeated five times per day for each patient and the posttest was conducted 5th day using the same tools. Results: The majority (n = 75, 75%) were 60-69 age group and 98% had education till primary school. 62% had diabetes and 20% of them had a history of peripheral arterial disease. 50% of participants had mildly impaired perfusion during pretest whereas abnormal neuropathy was seen in more than 70% cases which decreased posttest. A significant difference in PNS was seen after the implementation of BAE in both right LEP (t48 =6.81, p < 0.001) and left LEP t48 =5.21, p < 0.001). Conclusions: BAE has to be taught to the patients with DM in improving the level of LEP and can be encouraged to practice in the hospital and home care setup.